2012
DOI: 10.2527/jas.2012-5095
|View full text |Cite
|
Sign up to set email alerts
|

Effects of delayed steroid implanting on health, performance, and carcass quality in high health risk, auction market-sourced feedlot steers1,2

Abstract: Auction derived feeder calves (n=1,601; initial BW = 273.5 + 4.7 kg) were used to examine the effects of delayed administration of the initial steroid implant on health, performance, and carcass characteristics of feedlot cattle. Steers were procured from multiple- were obtained by USDA personnel; presence of lung lesions, pleural adhesions, and liver abscesses was evaluated by trained university personnel. Delaying the initial implant tended to reduce morbidity (24.7 vs. 28.5%; P = 0.13) and reduced railer ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
5
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 30 publications
1
5
0
Order By: Relevance
“…BRD has been associated with other non-infectious etiologies such as 3-methylindole (Bingham et al , 2000), nutritional interactions and deficiencies (Galyean et al , 1999), production management tools such as hormonal implanting (Munson et al , 2012), sourcing and prior or pre-weaning management (Smith, 1998; Reinhardt et al , 2009; Renter et al , 2013), and genetics (McAllister, 2010). A tremendous amount of work has investigated pathogen interactions related to both clinical and subclinical BRD.…”
mentioning
confidence: 99%
“…BRD has been associated with other non-infectious etiologies such as 3-methylindole (Bingham et al , 2000), nutritional interactions and deficiencies (Galyean et al , 1999), production management tools such as hormonal implanting (Munson et al , 2012), sourcing and prior or pre-weaning management (Smith, 1998; Reinhardt et al , 2009; Renter et al , 2013), and genetics (McAllister, 2010). A tremendous amount of work has investigated pathogen interactions related to both clinical and subclinical BRD.…”
mentioning
confidence: 99%
“…For instance, Kunkle et al (1980) reported no carryover effects on steer ADG when im planting 36 mg of zeranol during suckling, at weaning, and 84 to 120 d postweaning. Similarly, Munson et al (2012) reported no differences in ADG and G:F during a 187d feedlot period and carcass characteristics at slaughter between auction marketderived steers ad ministered a Revalor XS implant immediately at or 45 d after feedlot arrival. In summary, our results indicate that a 36mg zeranol implant could be administered simultaneously with other calf management procedures, such as wean ing, vaccination, and feedlot entry, without causing or enhancing the inflammatory response or impairing the overall vaccine response to BRDassociated patho gens.…”
Section: Preweaning(d−14to0)andpreconditioning(d 0 To 56) Phasesmentioning
confidence: 91%
“…In the current study, however, serum IBRV titers at the end of the preconditioning phase were increased when implant insertion was delayed by 14 d after wean ing compared to the remaining treatments. Munson et al (2012) reported a tendency toward lower morbidity rates (25% vs. 29%, respectively) for auction market derived steers that received a Revalor XS implant im mediately at or 45 d after feedlot entry. Our results on serum IBRV titers could provide a plausible explana tion for the results observed by Munson et al (2012).…”
Section: Preweaning(d−14to0)andpreconditioning(d 0 To 56) Phasesmentioning
confidence: 96%
See 1 more Smart Citation
“…Although ruminants may have a greater capacity to store digesta because of their larger digestive tracts, this weight loss and decrease in body condition may be comparable to the hypermetabolic state that develops in non-ruminants [3]. Munson et al [4] reported that delaying implant administration in high-risk calves did not alter feedlot performance or the risk of respiratory disease, suggesting that stress brought on by the transition to the feedlot did not diminish the anabolic signals from implanting early in the finishing phase.…”
Section: Introductionmentioning
confidence: 99%